Recent progress in the synthesis of novel two-dimensional van der Waals materials - Bian, Renji (2022)
The last decade has witnessed the significant progress of physical fundamental research and great success of practical application in two-dimensional (2D) van der Waals (vdW) materials since the discovery of graphene in 2004. To date, vdW materials is still a vibrant and fast-expanding field, where tremendous reports have been published covering topics from cutting-edge quantum technology to urgent green energy, and so on. Here, we briefly review the emerging hot physical topics and intriguing materials, such as 2D topological materials, piezoelectric materials, ferroelectric materials, magnetic materials and twistronic heterostructures. Then, various vdW material synthetic strategies are discussed in detail, concerning the growth mechanisms, preparation conditions and typical examples. Finally, prospects and further opportunities in the booming field of 2D materials are addressed.